The Relationship between Sex and Individual Gender in choosing physical activities (Journal of Hama University, 2021)
This research aims to verify whether some sports were a masculine domain and if physical activities were selected and practiced according to individual’s sex or gender or both. The sample consisted of 179 volunteers (99 male and 80 female), who were practicing various sportive activities which were classified as Maculin, feminin or Androgynous. The gender of the sample was determined by using the Arabic version of the BSRI: The Bem Sex-Role Inventory, valied by Madi and Salmeh (2017).The results showed that the number of males practicing sports activities was greater than females, adding that, in our syrian society, the selection of sports activities was consistent with typical sex stereotypes. As for gender, research proved that Femininity is the only gender that practices convenient sports activities rather than other types of gender.